The Arab Spring 2010: Puncak Gunung Es Krisis Politik di Kawasan Timur Tengah - Jatmika, Sidik (Jurnal Hubungan Internasional, 2013)
Since 2010, number of political uprisings took place in the Arab countries which so called The Arab Spring (at-ThawrÃ¢t al-âArabiyyah). The fall of regimes such as in Tunis, Egypt, and Libya, following the massive resistance of people was actually reflect the crisis of legitimacy and the weakness of authority of many political leaders in the region. Moreover, the loyalty of many people in the Arab countries to their leaders was also problematic decision when it has to deal with their primordial affiliations such as ashabiyah, wathanniyah, qaummiyah and ummah. The Arab Spring is a very important political movement which taught us lessons that both leadership and national character building are unfinished and will never be end as a process. This phenomenon also emphasized the importance of political system to be adaptive to the dynamic of domestic political situation and international atmosphere as well. The failure to adapt towards such conditions will causes to the fall of the ruling power.